Translation, validation and psychometric properties of Bahasa Malaysia version of the Significant Other Scale for Hearing Disability (SOS-HEAR) - Tengku Zam Zam, Tengku Zulaila Hasma; Dzulkarnain, Ahmad Aidil Arafat; Rahmat, Sarah; Jusoh, Masnira (2016)
Past studies have reported third-party disability exists among the significant other of the hearing-impaired with degree ranging from mild to severe. There are many available questionnaires that measure significant other’s psychosocial well-being following hearing impairment; and one that has been psychometrically validated and matched with WHO definition of third-party disability is the Significant Other Scale of Hearing Disability (SOSHEAR) (Scarinci, Worrall & Hickson, 2009). SOSHEAR which was developed in English consists of 27-items, assessing 5 general aspects; (i) Changes in communication, (ii) Changes in relationship, (iii) Going out and socializing, (iv) Emotional reactions to adaptations, and (v) concern for partner. All the 27 items in SOS-HEAR are not related to any cultural and religious perspective. Thus, SOSHEAR is potentially applicable to be used in Malaysia’s clinical context, yet language barrier remains an issue. Hence, our aim is to translate the English version of SOS-HEAR into Bahasa Malaysia and validate it. This process involves forward and backward translation by two-panellists. A harmonized version of the translated questionnaires will be psychometrically validated using response from 50 spouses of hearing-impaired patient. The translation of the SOS-HEAR into Bahasa Malaysia and the validation process will enable its use in audiology clinic in Malaysia as a tool to evaluate the existence and the degree of third-party disability among spouse of hearing impaired patients. Recognizing third-party disability among spouses’ of hearing-impaired patient is crucial in determining the direction of aural rehabilitation.